2001
DOI: 10.1039/b100482o
|View full text |Cite
|
Sign up to set email alerts
|

Potential of zero total charge of palladium modified Pt(111) electrodes in perchloric acid solutions

Abstract: The electrochemical behaviour of palladium-modiÐed Pt(111) electrodes in perchloric acid solutions has been studied by means of cyclic voltammetry and CO charge displacement. From the results of the charge displacement experiments, values of the potentials of zero total charge (pztc) have been determined and their dependence on the palladium coverage has been studied in solutions without speciÐcally adsorbing anions. These pztc values are compared to those obtained in sulfuric acid solutions. Whilst in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 42 publications
4
58
0
1
Order By: Relevance
“…Baldauf and Kolb [14] have attributed the more positive peak to hydrogen adsorption on the perimeter of Pd islands and the more negative peak to hydrogen adsorption on terraces. No H absorption was found at a monolayer of Pd in electrochemical conditions [13][14][15][16][22][23][24][25] but it seems to start even at coverages as low as 2 ML, as evidenced by the increase in current at the most positive potentials. This suggests that the growth of palladium on Au(1 1 1) is not exactly layer by layer after the first monolayer.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Baldauf and Kolb [14] have attributed the more positive peak to hydrogen adsorption on the perimeter of Pd islands and the more negative peak to hydrogen adsorption on terraces. No H absorption was found at a monolayer of Pd in electrochemical conditions [13][14][15][16][22][23][24][25] but it seems to start even at coverages as low as 2 ML, as evidenced by the increase in current at the most positive potentials. This suggests that the growth of palladium on Au(1 1 1) is not exactly layer by layer after the first monolayer.…”
Section: Methodsmentioning
confidence: 96%
“…It was suggested in the literature that the peaks in the presence of sulfuric acid may contain contribution due to the bisulfate adsorption, and the charge in perchloric acid is expected to be lower than in sulfuric acid considering the adsorption of (bi)sulfate anion in sulfuric acid and the absence of anion adsorption in perchloric medium.Álavarez et al [25] integrated cyclic voltammograms of 0.8 ML Pd on Pt(1 1 1) and found a total (anion and hydrogen adsorption) charge of 250 C cm −2 in perchloric acid and 265 C cm −2 in sulfuric acid. They also found, using CO displacement technique, that (bi)sulfate adsorption charge is 90 C cm −2 and in perchloric acid the anion adsorption charge is 50 C cm −2 .…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…The so-called CO displacement method has shown that (bi)sulfate is adsorbed on the palladium surface at potentials positive of the characteristic peaks in Figure 3, and hydrogen at potentials negative of them. [4,39] Though influenced by anion adsorption, the peak potentials serve as a measure for the hydrogenadsorption strength (the free enthalpy of adsorption can be derived directly from them) in such a solution. We assume that hydrogen adsorbs much stronger than sulfate, since the hydrogen peak potentials for sulfuric acid are more positive than the potentials of zero charge.…”
Section: Methodsmentioning
confidence: 99%
“…Durch Verdrängen der elektrischen Doppelschicht mit Kohlenmonoxid konnte gezeigt werden, dass negativ vom jeweiligen Strompeak in Abbildung 3 Wasserstoff und positiv davon (Hydrogen)-Sulfat adsorbiert ist. [4,39] Aus den Peakpotentialen kann die freie Adsorptionsenthalpie von Wasserstoff direkt abgeleitet werden, wobei wir annehmen, dass Wasserstoff viel stärker als Sulfat adsorbiert, da die Strompeaks in Schwefelsäure positiv vom Null-Ladungspotential liegen. [40] In atomen mit den Abständen zu den nächsten Nachbarn ändert; dies hat einen direkten Einfluss auf die Bindungsenergien.…”
Section: Elektrochemieunclassified